End-tidal carbon dioxide and defibrillation success in out-of-hospital cardiac arrest. (December 2017) - Savastano, Simone; Baldi, Enrico; Raimondi, Maurizio; Palo, Alessandra; Belliato, Mirko; Cacciatore, Elisa; Corazza, Valentina; Molinari, Simone; Canevari, Fabrizio; Danza, Aurora I.; De Ferrari, Gaetano M.; Iotti, Giorgio Antonio; et al.
Abstract: Purpose: Basing on the relationship between the quality of cardiopulmonary resuscitation (CPR) and the responsiveness of VF to the defibrillation we aimed to assess whether the values of ETCO2 in the minute before defibrillation could predict the effectiveness of the shock. Materials and methods: We retrospectively evaluated the reports generated by the manual monitor/defibrillator (Corpuls by GS Elektromedizinische Geräte G. Stemple GmbH, Germany) used for cases of VF cardiac arrest from January 2015 to December 2016. The mean ETCO2 value of the minute preceding the shock (METCO260 ) was computed. A blind evaluation of the effectiveness of each shock was provided by three cardiologists. Results: A total amount of 207 shocks were delivered for 62 patients. When considering the three tertiles of METCO260 (T1:METCO260 ≤ 20 mmHg; T2: 20 mmHg < METCO260 ≤ 31 mmHg and T3: METCO260 > 31 mmHg) a statistically significant difference between the percentages of shock success was found (T1: 50%; T2: 63%; T3: 78%; Chi square p = 0.003; p for trend <0.001). When the METCO260 was lower than 7 mmHg no shock was effective and when the METCO260 was higher than 45 mmHg no shock was ineffective. Shocks followed by ROSC were preceded by higher values of METCO260 as compared either to ineffective shocks or effective ones without ROSC. Conclusions: This is the first demonstration of the relation between ETCO2 and defibrillation effectiveness. Our findings stress the pivotal role of High Quality CPR, monitored via ETCO2, and suggest ETCO2 monitoring as an additional weapon to guide defibrillation.